Aberrant post-translational protein modifications in the pathogenesis of alcohol-induced liver injury - Osna, Natalie; Carter, Wayne; Ganesan, Murali; Kirpich, Irina A.; McClain, Criag J.; Petersen, Dennis R.; Shearn, Colin T.; Tomasi, Maria L.; Kharbanda, Kusum (Baishideng Publishing Group, 2016)
It is likely that the majority of proteins will undergo post-translational modification, be it enzymatic or non-enzymatic. These modified protein(s) regulate activity, localization and interaction with other cellular molecules thereby maintaining cellular hemostasis. Alcohol exposure significantly alters several of these post-translational modifications leading to impairments of many essential physiological processes. Here, we present new insights into novel modifications following ethanol exposure and their role in the initiation and progression of liver injury. This critical review condenses the proceedings of a symposium at the European Society for the Biomedical Research on Alcoholism Meeting held September 12-15, 2015, in Valencia, Spain.